SMILE and HAPPY: Novel Public Programs for Preventive Cardiology - Mosley, Mary (MD Conference Express, 2013)
The INTERHEART studies showed that 90% of cardiovascular disease (CVD) is linked to lifestyle factors. This article discusses the SMILE and HAPPY programs that promote preventative medicine.